Asthma from the patient's perspective. (March 2014) - Al-kalemji, Abir; Johannesen, Helle; Dam Petersen, Karin; Sherson, David; Baelum, Jesper
Abstract Background: Asthma is a chronic disease with considerable burden on health and economy. Despite growing knowledge about causes and treatment, many patients have uncontrolled asthma, activity and social limitations and reduced quality of life (QOL). Coping with asthma could be developed in a social and scientific context and influenced by personal experience. Objective: To investigate the asthmatic's perspective on asthma and how coping mechanisms with this disease were influenced by health professionals and networks. Methods: Asthma and QOL questionnaires were sent to 1191 individuals, who had participated in a population-based clinical study in 2004. Of the 7271 responders (72.7%), 10 chronic asthmatics (4 males and 6 females) with different asthma severity grades were recruited to in-depth interviews. The results were interpreted according to selected theories, especially Antonovsky's salutogenic theory on how comprehensibility, manageability and meaningfulness contribute to sense of coherence and successful coping with stressor/disease. Results and conclusion: Asthma comprehensibility was limited by both the lack of structured information about asthma diagnosis, treatment and prognosis and insufficient follow-up. The informants experimented with what worked and developed individual ways to accomplish satisfactory management. They adjusted their own medication and sometimes stopped prophylactic medicine as they did not detect an immediate effect. Many informants put their asthma into perspective, comparing it to what could have been worse. The unnoticeable development of asthma had probably triggered a gradual adaptation making it more complex for asthmatics to estimate severity. This together with their relative view of asthma might have led to gradual and uncritical accept of bothersome symptoms and reduced the need to seek professional advice or make important changes, e.g. eliminating exposure to irritating agents at work. Avoidance was a recurrent phenomenon as the asthmatics tended to drop physical activities with others instead of improving treatment. Several stated that they did not like to flash their asthma. They had concerns about being labelled as 'inadequate'. Physicians are urged to consider these tendencies and underlying the some of the mechanisms of 'living with asthma' in order to achieve proper asthma treatment and insure their patients' wellbeing.